Ethnobiology Study: Game in Dayak Lun Dayeh Community at Watershed of Mentarang in Malinau - Medi Hendra; Dijan Sunar Rukmi; Surianto Effendi; Freminci; Auliana (Jurnal Manajemen Hutan Tropika, 2023)
Dayak Lun Dayeh is one of local community who lives in East Kalimantan, where they’ve mostly practiced hunting traditionally, has particular ways to find hunting spot and use hunting techniques sustainably. The research about this community was conducted in river bank of Mentarang in order to determine the various kinds of game animal, frequently used hunting ground, and hunting ways of Dayak Lun Dayeh community at two different times, on May-July 2016 and June-August 2021. Research data were collected through open ended interviews (assisted by key informants), field observations and animal photos. Data were presented descriptively by ethnobiology approach. The results showed that this community practices subsistence hunting of wild animals, which comprised of mammals (69-73%), reptiles (14-15%), aves (8%) and amphibians (0-4%). The meat obtained from hunting(s) were consumed as protein source, served as medium in traditional ceremonies or religious rituals based on ancestral teachings. Wild animals such as Cervus unicolor, Sus barbatus, Muntiacus atherodes could be found easily in abpa’ nuvan (salt lick) rather than primary forest, swidden (latii), swidden fallow (included amug, jekau and ripa), farm, river, or secondary forest such as the logging roads of former timber company. Several hunting techniques were applied such as using hunting dogs for tracking the game animals (gelibut), sieging or waiting (gabang) at specific location (abpa’ nuvan), and setting traps (ton).